Análisis de índice de vegetación y temperatura superficial terrestre para la delimitación de la isla de calor en la ciudad de Junín - Cedeño García, Carlos Paul (2026)
This research project aimed to analyze the Urban Heat Island (UHI) in the city of Junín, Manabí, through the analysis of the Normalized Difference Vegetation Index (NDVI) and the Land Surface Temperature (LST), to understand the impact of urban growth on the local microclimate and propose mitigation strategies. The methodology was divided into three phases, using remote sensing and Geographic Information Systems (GIS) to process satellite data from the years 2016, 2020, and 2024. In the first phase, the condition of green areas was examined, revealing that the highest NDVI values of 0.51 are found on the periphery of the city, while the urban core presents low or no vegetation coverage of 0.02. The second phase evaluated the LST, confirming that the areas with the least vegetation in the urban center recorded the highest temperatures, reaching 31.20°C. Finally, the third phase quantified the intensity of the UHI, establishing a clear inverse correlation between NDVI and the UHI. The results demonstrate that areas with sparse vegetation are the most affected by the heat island phenomenon, which has significant implications for public health and quality of life. The findings of this study reaffirm the importance of green areas as heat mitigators and the need to integrate urban planning with environmental sustainability.